2011
DOI: 10.1016/j.biochi.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular organizations in the aerobic respiratory chain of Escherichia coli

Abstract: a b s t r a c tThe organization of respiratory chain complexes in supercomplexes has been shown in the mitochondria of several eukaryotes and in the cell membranes of some bacteria. These supercomplexes are suggested to be important for oxidative phosphorylation efficiency and to prevent the formation of reactive oxygen species.Here we describe, for the first time, the identification of supramolecular organizations in the aerobic respiratory chain of Escherichia coli, including a trimer of succinate dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
(41 reference statements)
5
36
0
Order By: Relevance
“…Protein concentration was determined using the bicinchoninic acid (BCA) protein assay from Pierce (Smith et al, 1985). Membrane solubilization was performed with 6 g digitonin per gram of protein, in a buffer containing 50 mM NaCl, 5 mM aminocaproic acid, 1 mM EDTA, 2 mM PMSF and 50 mM imidazole/HCl, pH 6, as previously described (Sousa et al, 2011). Solubilized membranes (150 mg per lane) were resolved in a 3-10 % acrylamide gradient blue native-PAGE (BN-PAGE) gel (Krause & Seelert, 2008;Schägger & von Jagow, 1991;Wittig et al, 2006), and NADH : NBT (nitro blue tetrazolium) and succinate : NBT oxidoreductase activities were detected in the gel (Zerbetto et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Protein concentration was determined using the bicinchoninic acid (BCA) protein assay from Pierce (Smith et al, 1985). Membrane solubilization was performed with 6 g digitonin per gram of protein, in a buffer containing 50 mM NaCl, 5 mM aminocaproic acid, 1 mM EDTA, 2 mM PMSF and 50 mM imidazole/HCl, pH 6, as previously described (Sousa et al, 2011). Solubilized membranes (150 mg per lane) were resolved in a 3-10 % acrylamide gradient blue native-PAGE (BN-PAGE) gel (Krause & Seelert, 2008;Schägger & von Jagow, 1991;Wittig et al, 2006), and NADH : NBT (nitro blue tetrazolium) and succinate : NBT oxidoreductase activities were detected in the gel (Zerbetto et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Solubilized membranes (12.5 mg) were also applied to the top of a continuous sucrose gradient (0.3-1.5 M) in a buffer containing 15 mM Tris/HCl, pH 7, 20 mM KCl and 0.2 % digitonin, resolved by ultracentrifugation at 4 uC (20 h, 150 000 g) (Dudkina et al, 2005;Sousa et al, 2011) and collected in 1 ml fractions. Membrane samples (50 or 100 mg) were resolved by SDS-PAGE (Laemmli, 1970), transferred onto a PVDF membrane essentially according to (Towbin et al, 1979), and detected with polyclonal antibodies against subunits of respiratory chain complexes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2B). Crystal structure and BN-PAGE data have shown that functional SDH is trimeric with a molecular mass of 360 kDa (33,34). Finally, native WT and ⌬sdhE membranes were separated by BN-PAGE (Fig.…”
Section: Loss Of Sdhe Does Notmentioning
confidence: 99%